Qualidade de vida relacionada à saúde, depressão e ansiedade de profissionais atuantes na linha de frente no cuidado às pessoas com Covid-19 - Nascimento, Nathalia Claudino do (2022)
Introduction: On the world stage, although distant from our daily lives, the beginning of 2020 was marked by an outbreak of a mysterious pneumonia caused by a variation of the coronavirus whose first case was reported in December 2019 in the city of Wuhan, China. Therefore, the health system and professionals are overloaded, exposing their lives to the risk of illness on a daily basis. Therefore, it is necessary to evaluate the possible implications arising from the covid-19 pandemic for health professionals who worked on the front line. Objective: To assess the health-related quality of life of health professionals working on the front lines of covid-19 and its association with sociodemographic characteristics and possible physical and emotional implications. Methodology: A cross-sectional study was carried out with 123 health professionals working on the front line of covid-19, in a university hospital in the municipality of João Pessoa, Paraíba. Due to the health restrictions imposed by the pandemic period, the survey took place online in which participants received the questionnaire through the social network Whatsapp. Instruments were used for sociodemographic characterization, the Hospital Anxiety and Depression Scale (HAD) and the Quality of Life Assessment Scale - Short Form-36. In the analysis, absolute and relative frequencies were used for sociodemographic variables; the scores of the Hospital Anxiety and Depression Scale were analyzed individually using Pearson's Chi-square test and the Mann- Whitey test was used to analyze the domains of the Short Form-36 scale. The project - CAAE: 46478921.9.0000.5183 was approved by the Research Ethics Committee, according to opinion: 4.717.692. Results: The assessment of health professionals showed significant results for all domains of the Short Form-36 scale, in which those with symptoms of anxiety and depression had worse scores in the domains of health-related quality of life. According to the Hospital Anxiety and Depression Scale, professionals who were absent from the family environment are more likely to develop depression and anxiety, on the other hand, the presence of a child was considered a protective factor for anxiety. Conclusions: It was identified that health professionals who remained absent from their family environment were more likely to develop symptoms of anxiety and depression; and, those who presented such symptoms had significant impairments in the assessment of health-related quality of life. Thus, the importance of caring for the physical and mental health of these workers is demonstrated so that the impacts resulting from working on the front line in a pandemic situation minimally affect their mental health and consequently their health-related quality of life.